Differential Sandwich Theorems of Analytic Functions Defined by Linear Operators (European Journal of Pure and Applied Mathematics, 2011)
In this paper, we obtain some applications of first order differential subordination and superordination results involving a linear operator and other linear operators for certain normalized analytic functions. Some of our results generalize previously known results.